Genetic variability and fumonisin B₁ production of Fusarium proliferatum and Fusarium verticillioides associated with diseased plants - Azman, Najihah (2018)
Several Fusarium species are plant pathogen that can cause various diseases on fruits and vegetables. The common Fusarium species that can infect plants are Fusarium proliferatum and Fusarium verticillioides. Ear rot on maize, Fusarium wilt on cucurbits, fruit rot on tomato and banana are diseases caused by these two species. Both species are able to produce fumonisin B1 (FB1) that are harmful towards human and animal and currently there is a lack of information regarding the effect from exposure of FB1. Thus, the objectives of this study were to identify F. proliferatum and F. verticillioides based on speciesspecific primers using polymerase chain reaction (PCR), to evaluate the genetic diversity between both species based on microsatellite marker, to detect the production of FB1 by both species and to examine embryotoxicity effect of FB1 on the larvae of zebrafish (Danio rerio). Fifty isolates of Fusarium species were obtained from different hosts throughout Malaysia. All isolates were identified using species-specific primers of which 29 isolates were identified as F. proliferatum and 21 isolates as F. verticillioides. The genetic diversity of the isolates was evaluated using six established microsatellite primers. Five out of six primers amplified polymorphic bands with primers showed high number of alleles were (AG)7C and (TCC)5. Meanwhile one primer (TTTC)4 gave negative result with no band amplified. The constructed phylogenetic tree showed two different clades distinguished between F. proliferatum and F. verticillioides and high diversity among the clades according to different hosts and locality. Successful amplification of the FUM1 gene showed the presence of this gene in the genome of 48 out of 50 isolates. Fusarium proliferatum produced FB1 ranged from 16.48-6677.32 ppm. Meanwhile F. verticillioides produced FB1 ranged from 12.26-954.01 ppm. From the assessment of embryotoxicity test of FB1 on larvae of zebrafish, five concentrations of FB1 (0.43, 0.58, 0.72, 0.87 and 1.00 ppm) were tested. Morphological changes of heart, yolk sac and spine of the FB1 exposed-larvae were observed at 24 to 168 hours post-fertilization (hpf). The mortality rate and abnormality of zebrafish larvae’s were significantly increased at 144 hpf exposure. Pericardial edema and yolk sac edema was severely observed at concentration 0.72–1.00 ppm at 120 hpf exposure meanwhile spinal curvature can be observed at all concentrations at 168 hpf. Spontaneous tail coiling showed significant difference to the normal whereas no significant differences on the heart rate. As a conclusion, F. proliferatum and F. verticillioides can be identified by using species-specific primers. These two species have showed high diversity among the isolates based on microsatellite and phylogenetic analyses.